2013
DOI: 10.7314/apjcp.2013.14.6.3861
|View full text |Cite
|
Sign up to set email alerts
|

Risk Effects of GST Gene Polymorphisms in Patients with Acute Myeloid Leukemia: A Prospective Study

Abstract: Glutathione S-transferase (GST) enzyme levels are associated with risk of many cancers, including hematologic tumours. We here aimed to investigate the relationships between GSTM1, GSTT1 and GSTP1 polymorphisms and the risk of AML. Genotyping of GSTs was based upon duplex polymerase-chain-reactions with the confrontingtwo-pair primer (PCR-CTPP) method in 163 cases and 204 controls. Individuals carrying null GSTT1 genotype had a 1.64 fold risk of acute leukemia relative to a non-null genotype (P<0.05). A heavy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 21 publications
(22 reference statements)
2
19
0
2
Order By: Relevance
“…Such cancers include lung cancer (Mir Muhammad NasirUddin, 2014), ovarian cancer (Coughlin and Hall, 2002) and breast cancer (Hashemi et al, 2012). Previous studies have reported about GSTs association with heamatological malignancy, but with conflicting findings as mentioned previously (Dunna et al, 2012;Zhou et al, 2013;Rostami internal positive control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such cancers include lung cancer (Mir Muhammad NasirUddin, 2014), ovarian cancer (Coughlin and Hall, 2002) and breast cancer (Hashemi et al, 2012). Previous studies have reported about GSTs association with heamatological malignancy, but with conflicting findings as mentioned previously (Dunna et al, 2012;Zhou et al, 2013;Rostami internal positive control.…”
Section: Discussionmentioning
confidence: 99%
“…(Hashemi et al, 2012). The GSTM1 null and GSTT1 null appear to be associated with a significant risk of several types of cancers, such as hematological neoplasm (Banescu et al, 2014;Sailaja et al, 2010;Zhou et al, 2013) and breast cancer (Hashemi et al, 2012). It has been shown that the risk of ALL is doubled in patients who carry the GSTM1 deletion (Joseph et al, 2004).…”
Section: Genotypesmentioning
confidence: 99%
“…Detailed process for selecting eligible studies was showed in Figure 1. Among these, two studies (Dunna et al, 2012;Zhou et al, 2013) were excluded for HWE deviation. Finally, 23 studies, which control individuals did not departure from HWE (P-value of HWE >0.05, respectively), were included in the metaanalysis.…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…Acute myeloid leukemia (AML) is a clonal disorder that is characterized by the abnormal accumulation of white blood cells in the bone marrow and which interferes with the normal production of blood cells (1). The etiology of AML was found to be multifactorial; however, exposure to carcinogens such as benzene and ionizing radiation is thought to result in DNA damage at the level of hematopoietic progenitor cells, which is an essential prerequisite for the development of AML (2).…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of the GSTP1 Ile105Val genotypes in controls was not in accordance with the HWE in five studies and hence, they were excluded (1,11,16,31,35). A meta-analysis was conducted using the data of 852 cases and 2339 controls from additional five studies under the allele contrast (Fig.…”
mentioning
confidence: 99%